Isolation and Characterization of a Cholesterol-Lowering Bacteria from Bubalus bubalis Raw Milk - Abdul Hameed; Carla Condò; Isfahan Tauseef; Maryam Idrees; Shakira Ghazanfar; Arshad Farid; Muhammad Muzammal; Mohammed Al Mohaini; Abdulkhaliq J. Alsalman; Maitham A. Al Hawaj; Charles Oluwaseun Adetunji; Wadzani Palnam Dauda; et al. (Fermentation, 2022)
Probiotics retrieved from animal sources have substantial health benefits for both humans and animals. The present study was designed to identify lactic acid bacteria (LAB) isolated from domestic water buffalo milk (Bubalus bubalis) and to evaluate their potential as target-based probiotics. Forty-six LAB strains were isolated and, among them, five strains (NMCC-M2, NMCC-M4, NMCC-M5, NMCC-M6, and NMCC-M7) were regarded as possible probiotics on the basis of their phenotypic and biochemical properties. These isolates were molecularly identified as Weissella confusa (NMCC-M2), Leuconostoc pseudo-mesenteroides (NMCC-M4), Lactococcus lactis Subsp. hordniae (NMCC-M5), Enterococcus faecium NMCC-M6, and Enterococcus lactis NMCC-M7. The tested bacterial strains showed significant antimicrobial activity, susceptibility to antibiotics, acid and bile tolerance, sugar fermentation, enzymatic potential, and nonhemolytic characteristics. Interestingly, NMCC-M2 displayed the best probiotic features including survival at pH 3 and 0.5% (w/v) bile salts, complete susceptibility to the tested antibiotics, high enzymatic potential, and in vitro cholesterol reduction (48.0 µg/mL for NMCC-M2) with 0.3% bile salt supplementation. Therefore, the isolated strain NMCC-M2 could be considered as a potential target-based probiotic in cholesterol-lowering fermented food products.